LSD1 inhibition by tranylcypromine hydrochloride reduces alkali burn-induced corneal neovascularization and ferroptosis by suppressing HIF-1α pathway - Qian Deng; Yuelan Gao; Yujin Wang; Jiewen Mao; Yulin Yan; Zixian Yang; Yuyu Cong; Yanning Yang; Shanshan Wan (Frontiers Media S.A., 2024)
BackgroundCorneal neovascularization (CNV) is a sight-threatening condition that necessitates epigenetic control. The role of lysine-specific demethylase 1 (LSD1) in CNV remains unclear, despite its established significance in tumor angiogenesis regulation.MethodsAn alkali burn-induced CNV mouse model was used in vivo. The effects of LSD1 inhibitor tranylcypromine hydrochloride (TCP) were examined through slit lamp, histological staining, and immunofluorescence. The expression of malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione (GSH) levels were assessed in corneal tissues. Oxidative stress and ferrous ion expression during CNV were determined using 4-HNE, GPX4, and FerroOrange staining. In vitro, a hypoxia-reoxygenation (H/R) model was established using human umbilical vein endothelial cells (HUVECs) to study LSD1 or hypoxia-inducible factor (HIF-1α) knockdown and lentiviral overexpression of HIF-1α. The effects on HUVECs migration, invasion, and angiogenesis were evaluated through cell scratching assay, transwell migration assay and tube formation assay. The role of ferroptosis was investigated using ROS staining, FerroOrange staining, and key ferroptosis proteins. Further, The JAK2/STAT3 pathway's involvement in CNV regulation was explored through in vivo experiments with subconjunctival injection of AG490.ResultsThe results showed a substantial correlation between corneal damage and LSD1 levels. In addition, HIF-1α expression was also elevated after alkali burns, and subconjunctival injection of TCP reduced corneal inflammation and neovascularization. Corneal alkali burns increased ROS levels and reduced antioxidative stress indicators, accompanied by elevated ferrous ion levels, which were reversed by TCP injection. In vitro, TCP or siRNAs inhibited H/R-induced ferroptosis and angiogenesis in HUVECs by affecting specific protein expressions and MDA, SOD, and GSH levels. HIF-1α levels, associated with ROS production, ferroptosis, and angiogenesis, increased during H/R, but were reversed by TCP or siRNA administration. HIF-1α overexpression counteracted the effects of LSD1 inhibition. Additionally, AG490 injection effectively reduced HIF-1α and VEGFA expression in the CNV model.DiscussionThese findings suggest that LSD1 inhibition via the HIF-1α-driven pathway prevents angiogenesis, oxidative stress, and ferroptosis in corneal alkali burn-induced CNV, highlighting LSD1 as a potential therapeutic target.